Pengaruh Berkumur Air Kelapa (Cocos nucifera) terhadap Laju Aliran Saliva - Wowor, Vonny N. S.; Mariati, Ni Wayan; Depthios, Richard F. (e-GiGi, 2025)
Abstract: Decreased salivary flow rate can be caused by many things, inter alia age, consumption of certain drugs, and psychological effects. The benefits of coconut water have been widely studied, one of which is related to dental and oral health. However, there are still not many studies about the effects of various varieties of coconut water in increasing the flow rate of saliva, especially old coconut water which is often thrown away as waste. This study aimed to determine whether there was an effect of coconut water (Cocos nucifera) gargling on the rate of salivary flow. This was an experimental and analytical study with a quasi-experimental design, and pre-test and post-test control group design approaches. Samples were dentistry undergraduate students of Universitas Sam Ratulangi taken by simple random sampling. Samples were divided into two groups: treatment group (gargling with old coconut water) and control group (gargling with mineral water). The results showed that in the treatment group, there was an increase of salivary flow rate from 0.7114 to 1.1248 after gargling with old coconut water. Meanwhile, in the control group, there was an increase of salivary flow rate from 0.7962 to 0,8495 after gargling with mineral water. Since research data were normally distributed and homogenous, the statistical analysis was continued with the unpaired T-test which obtained a p-value of <0.001 (p<0.05). In conclusion, coconut water (Cocos nucifera) gargling can influence the salivary flow rate. Keywords: coconut water; salivary flow rate; gargling   Abstrak: Laju aliran saliva yang menurun dapat diakibatkan oleh berbagai hal antara lain faktor usia, mengonsumsi obat-obatan tertentu, dan efek psikis. Manfaat air kelapa terhadap kesehatan antara lain kesehatan gigi dan mulut telah diteliti namun belum banyak penelitian mengenai efek air kelapa dari berbagai varietas dalam hal meningkatkan laju aliran saliva terutama air kelapa tua yang masih sering dibuang sebagai limbah. Penelitian ini bertujuan untuk mengetahui pengaruh berkumur air kelapa (Cocos nucifera) terhadap laju aliran saliva. Jenis penelitian ialah eksperimental dengan rancangan quasi eksperimental, dan pendekatan pre test dan post test control group design. Sampel penelitian ialah mahasiswa S1 PSPDG Fakultas Kedokteran Universitas Sam Ratulangi yang diambil secara simple random sampling dan dibagi atas dua kelompok, yaitu kelompok perlakuan (berkumur air kelapa tua) dan kelompok kontrol (berkumur air mineral). Hasil penelitian mendapatkan pada kelompok perlakuan rerata laju aliran saliva sebelum dan setelah berkumur air kelapa naik dari 0,7114 menjadi 1,1248 sedangkan pada kelompok kontrol rerata laju aliran saliva sebelum dan setelah berkumur air mineral naik dari 0,7962 menjadi 0,8495. Oleh karena data penelitian berdistribusi normal dan homogen, dilanjutkan dengan uji t tidak berpasangan yang mendapatkan nilai p<0,001 (p<0,05). Simpulan penelitian ini ialah berkumur air kelapa (Cocos nucifera) dapat meningkatkan laju aliran saliva. Kata kunci: air kelapa; laju aliran saliva; berkumur